Partisipasi Perempuan dalam Penyusunan Reusam Perlindungan Anak di Tingkat Gampong di Aceh Besar - Mansari Mansari; Muslim Zainuddin (Kafa`ah: Journal of Gender Studies, 2019)
Women have a smaller part  of participation in creating creating gampong reusam (village rules) that regulate the children. The women participation is crucial in meeting the gender based role representation. This research aimed to know more about women mechanism and their participatio now  and the process how they are actively involved in formulating Gampong Reusam in Aceh Besar. The compilation was done by doing the deliberation in meunasah and balee (balai) by involving the social elements, especially in gampong, involves women and children figures. To  invite the woman, the committee uses loudspeaker in meunasah and delivered orally by Keuchik (the village leader). Involvement of women is usually done by invited by loudspeakers in meunasah and also delivered orally by Keuchik (Village Head). The presence of women has not been maximized in the attempt of preparing the reusam gampong because the arrangement is done at night, time to rest, keeping the children at home, the weather is not supporting because of the rain. The role of women in the village reusam has been represented in the context of the handling of children against the law.